2014
DOI: 10.1093/ejcts/ezt593
|View full text |Cite
|
Sign up to set email alerts
|

Ablation in selective patients with long-standing persistent atrial fibrillation: medium-term results of the Dallas lesion set

Abstract: The Dallas lesion set is an effective treatment in patients with LSPAF. It resulted in significant improvement in LA volume and function after restoration of sinus rhythm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
1
11
0
5
Order By: Relevance
“…Despite all new insights and development in clinical practice, long‐term rhythm control in patients with AF remains a major challenge, particularly for patients with (long‐standing) persistent and postablation AF. Past studies that have focused on long‐term rhythm outcome after (hybrid) thoracoscopic ablation have reported success rates varying between 38% and 83% up to 5 years, depending on follow‐up duration, AF subtype (paroxysmal vs nonparoxysmal) and antiarrhythmic drug usage, as shown in Table . As can be observed from this quick overview, the 60% success rate in our study is similar to what most of these studies have reported and confirms the steady reasonable results after thoracoscopic AF ablation.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Despite all new insights and development in clinical practice, long‐term rhythm control in patients with AF remains a major challenge, particularly for patients with (long‐standing) persistent and postablation AF. Past studies that have focused on long‐term rhythm outcome after (hybrid) thoracoscopic ablation have reported success rates varying between 38% and 83% up to 5 years, depending on follow‐up duration, AF subtype (paroxysmal vs nonparoxysmal) and antiarrhythmic drug usage, as shown in Table . As can be observed from this quick overview, the 60% success rate in our study is similar to what most of these studies have reported and confirms the steady reasonable results after thoracoscopic AF ablation.…”
Section: Discussionsupporting
confidence: 88%
“…Totally thoracoscopic epicardial ablation has evolved over the last decade towards a successful and safe minimally invasive rhythm control strategy, with a Class 2A indication, for patients with symptomatic drug refractory (long‐standing) persistent and postablation atrial fibrillation (AF) . The procedure is associated with a 79% freedom from AF after 2 years, but evidence for long‐term durability is still limited with reported success rates varying between 38% and 83% after a follow‐up up to 5 years . In addition, AF is associated with threefold to fivefold higher stroke rates, but information on the long‐term stroke risk after thoracoscopic ablation remains limited to a few studies reporting a low cerebrovascular event rate .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19) [815]. W celu poprawy wyników leczenia [468,[816][817][818] wykonywano bardziej rozległe uszkodzenia, w tym linie łączące między miejscami PVI (uszkodzenie typu "pudełka"; box lesion) oraz linie biegnące w kierunku pierścienia mitralnego [812,[819][820][821][822]. W celu poprawy wytwarzania pełnościennych uszkodzeń [716] zaproponowano www.kardiologiapolska.pl ostatnio strategie ablacji od strony wsierdzia i nasierdzia [812,[823][824][825].…”
Section: Oddzielne Zabiegi Chirurgiczne W Celu Kontroli Rytmu Sercaunclassified
“…Decyzje dotyczące takich pacjentów powinny zostać poparte przez kardiogrupę (Heart Team) ds. leczenia AF IIa B [468,812,819,823] Operacja labiryntowania, najlepiej z dostępu minimalnie inwazyjnego, wykonywana w doświadczo-nym ośrodku przez odpowiednio wyszkolonego operatora, powinna być rozważana przez kardiogrupę (Heart Team) ds. leczenia AF jako metoda terapii pacjentów z objawowym, opornym na leczenie przetrwałym AF lub AF po ablacji w celu zmniejszenia objawów IIa C [808,832] Operacja labiryntowania, najlepiej obejmująca oba przedsionki, powinna być rozważana w celu zmniejszenia objawów przypisywanych AF u pacjentów poddawanych operacji kardiochirurgicznej, z uwzględnieniem dodatkowego ryzyka zabiegowego i korzyści z leczenia w celu kontroli rytmu serca [362] prób klinicznych z użyciem NOAC [39] oraz analiz przeprowadzonych u starszych Amerykanów (Medicare) [396].…”
Section: ]unclassified